BOOK REVIEWS (Journal of Finance, 1980)
Book reviewed in this article: FINANCIAL MANAGEMENT: “Capital Investment and Financial Decisions.” By HAIM LEVY and MARSHALL SAR‐NAT INVESTMENTS: Stocks, Bonds, Bills and Inflation: The Past (1926”“1976) and the Future (1977”2000 ), by ROGER G. IBBOTSON and REX A. SINQUEFIELD. MACRO”FINANCE: A Micro” to” Macro Model of the Swedish Economy . Papers on the Swedish Model from the Symposium on Micro Simulation Methods in Stockholm September 19”22, 1977. Ed. By GUNNAR ELIASSON. MACRO” FINANCE: Prospects for Capital Formation and Capital Markets . By ARNOLD SAMETZ. BANKING: The Origins of Central Banking in the United States . By RICHARD H. TIMBERLAKE, JR. BANKING: Money and Credit in a Developing Economy: The Greek Case . By D. J. HALIKIAS. PUBLIC FINANCE: Must Corporate Income Be Taxed Twice? By CHARLES E. McLURE, JR. INTERNATIONAL FINANCE: International Monetary Issues and Development Policies: Selected Essays and Statements By XENOPHON ZOLOTAS